Biopsychosocial Factors Associated with Depression Among U.S. Undergraduate International Students - Zeng, Fanyi; Brunsting, Nelson; Brocato, Nicole; Kiang, Lisa; Jayawickreme, Eranda; Kathuria, Sonali (Journal of International Students, 2021)
Using a biopsychosocial framework, our study examines the biological, psychological, and sociocultural factors associated with depression among a crosssectional sample of undergraduate international students (N = 712) attending 28 U.S. colleges and universities. Consistent with hypotheses, regression analysis reveals that self-esteem, life satisfaction, and coping self-efficacy are negatively associated with depressive symptoms, and that ethnic minority status, perceived discrimination, and financial concerns are positively associated with depressive symptoms. Contrary to predictions, age, optimism, friendships, and school belonging are not significant predictors, and perseverance predicted increases depression in this sample. The novel findings highlight adaptation issues among international undergraduate students and suggest preventive measures and interventions against depression for university administrators and counselors.